Pemanfaatan Limbah Biomassa Ampas Tebu sebagai Energi TerbarukanPada Pembangkit Listrik Tenaga Biomassa (PLTBM) di PG. Glenmore - Tegar Trikora Adi (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
Biomass is waste from industry and household waste, so utilizing biomass is a way to overcome waste problems. As the population increases and fossil fuel reserves become increasingly depleted, new and renewable alternative fuels that are environmentally friendly, effective and efficient are urgently needed. One of the new and renewable alternative energy sources is sugarcane bagasse biomass. In steam power plants, fuel is an important part of the power generation process device. The type of fuel is also always a consideration because fuel is the main device for generating steam electricity. Apart from diesel, sugarcane bagasse is also an option as a fuelfor power plants. Comparison of economic analysis costs for bagasse = IDR 20,097,001/hour Coal = IDR 39,193,190/hour to produce 11 MW of electricity. So bagasse can be used as fuel which is more economical in terms of fuel procurement costs compared to coal